Gerhard Tintner. Methodology of mathematical economics and econometrics. Chicago : University of Chicago Press, 1968. 113 p. - Cosío Pascal, Enrique (Estudios Demográficos y Urbanos, 1969)
GERHARD TINTNER, Methodology of Mathematical Economics and Econometrics. Chicago, University of Chicago Press, 1968.